Sosialisasi dan Pelatihan Manajemen Sumber Daya Manusia (MSDM) Sederhana pada Herman Konveksi di Medan - Patar Marbun; Eryanti Novita; Teddi Pribadi (Universitas Pahlawan Tuanku Tambusai, 2026)
Human Resource Management (HRM) training is crucial for an organization, and work morale is equally important. Work morale can be a key competitive advantage when it supports an organization's strategy. Having a strategy for running a business is crucial for survival in the current competitive and sluggish economic climate. The challenges facing MSMEs are the need to improve human resource competency, build and strengthen work morale, and enhance strategic management and skills to improve MSME performance and survive amidst today's fierce competition. Essentially, human resource competency still needs to be improved to raise awareness of the importance of competence and foster a better work morale for survival and sustainability. The purpose of this community service activity is to provide training to improve human resource competency.